Development of CdS/TNTA nanocomposite to improve performance of simultaneous electrocoagulation-photocatalysis process for hydrogen production and ciprofloxacin elimination - Reno Pratiwi; Muhammad Ibadurrohman; Eniya Listiani Dewi; Ratnawati; Rike Yudianti; Saddam Husein; Slamet (Materials Science for Energy Technologies)
This study aimed to enhance the effectiveness of the simultaneous combination of electrocoagulation and photocatalysis processes by modifying the configuration of the photocatalyst. A heterojunction mechanism was developed by integrating CdS with a photocatalyst using a TiO2 nanotube array (TNTA) [1]. This mechanism is designed to enhance photocatalytic efficiency by reducing electron-hole recombination. The successful synthesis of CdS/TNTA nanocomposite was confirmed using various characterization methods, including XRD, HRTEM, FESEM, UV–Vis DRS, PL, transient photocurrent, and XPS. The results showed that CdS/TNTA worked better than TNTA in a single photocatalysis process, achieving improved Ciprofloxacin (CIP) removal (7.9 % to 13.8 %) and hydrogen gas production (0.006 to 0.156 mmol/m2plate). Simultaneously operating electrocoagulation and photocatalysis systems in the respective optimized settings resulted in significant enhancements. Hydrogen gas yield increased by 44 % (from 443 to 636 mmol/m2 plate) compared to using only TNTA, while CIP removal improved from 79 % to 83 %. This study demonstrates that the synthesis of CdS/TNTA photocatalysts may be a promising approach to achieving high performance of hydrogen recovery while simultaneously removing CIP from wastewater.